033 GLP-1RAs reduce stroke incidence in patients with type 2 diabetes mellitus: a meta-analysis. Issue 6 (27th May 2022) - Maskery, Mark; Wall, Jasmine; Holscher, Christian; Jones, Stephanie; Price, Christopher; Strain, David; Watkins, Caroline; Werring, David; Emsley, Hedley
Abstract : Background: Patients with Type 2 Diabetes Mellitus (T2DM) are at a relatively higher risk of severe stroke. Glucagon like peptide-1 receptor agonists (GLP-1RAs) are licensed for the management of T2DM. Cardio- vascular outcome trials (CVOTs) have demonstrated that GLP-1RAs can be safely administered to T2DM patients but have also indicated a trend towards a reduction in non-fatal stroke incidence compared to placebo. Methods: We searched the literature to identify all GLP-1RA CVOTs. We performed a meta-analysis of the incidence of non-fatal stroke and presented the outcomes by Odds Ratio (OR) with 95% confidence intervals (CI). Results: We identified 7 GLP-1RA studies. SUSTAIN-6 and REWIND reported statistically significant reductions in non-fatal stroke incidence, whilst LEADER demonstrated a similar, non-significant trend. ELIXA, EXSCEL, HARMONY and PIONEER-6 did not report a reduction in stroke incidence. Meta-analysis of 7 studies, totalling 56, 004 participants yielded a significant reduction in non-fatal stroke incidence in patients receiving GLP-1RAs when compared with placebo (OR 0.85, 95% CI 0.76 – 0.94). Conclusions: This data supports the value of GLP-1RAs in reducing stroke incidence in patients with T2DM. There is potential value in prospective, randomised controlled trials adequately powered to establish the value of GLP-1RAs in stroke prevention in T2DM patients. mark.maskery@doctors.org.uk|ABN Bursary